Adipose stem cells promote smooth muscle cells to secrete elastin in rat abdominal aortic aneurysm. - Xiaohong Tian (Public Library of Science (PLoS), 2014)
Background Abdominal aortic aneurysm (AAA) is a life-threatening disease and its prevalence rate increases with social aging. The degradation of elastic is an important factor in the formation of AAA. Methods Adipose derived stem cells (ADSCs) and bone marrow mesenchymal stem cells (BMSCs) were isolated from rats, and identified by Oil red O and alizarin red staining after adipogenesis and osteogenesis induction. In addition, ADSCs were also identified by flow cytometry with CD markers. AAA model in rats was established, and smooth muscle cells (SMCs) were isolated from AAA aortic wall and identified by immunohistochemistry. ADSCs or BMSCs were co-cultured with AAA aortic wall for in vitro experiment, and ADSCs were injected into AAA model for in vivo test. Then orcein staining was used for observing the morphology of elastic fiber, Western blot and real-time PCR were used respectively to detect the protein and gene expression of elastin, gelatinases spectrum analysis was used to detect the activity of matrix metalloproteinase-2 (MMP-2) and MMP-9. Results Lots of red lipid droplets were visible by Oil red O staining after adipogenesis induction, and black calcium nodules appeared by alizarin red staining after osteogenesis induction. The results of flow cytometry showed that ADSCs expressed CD44 and CD105, but exhibited negligible expression of CD31 and CD45. SMCs exhibited spindle-like morphology and α-actin protein was positive in cytoplasm. After co-cultured with ADSCs or BMSCs, the elastic fiber recovered normal winding shape, both the gene and protein expression of elastin increased, and the activity of MMP-2 decreased. The in vivo result was similar to that of in vitro. Conclusions ADSCs promote the expression of elastin in SMCs and contribute to the reconstruction of elastic fiber, which may provide new ideas for treating AAA.